Development of Assessment Instruments for Scientific Literacy Skills Tests for VII Grade Junior High School Students on Global Warming Material - Adisti Yuliastrin; Deska Indri Yani; Rian Vebrianto (JURNAL PENDIDIKAN MIPA, 2025)
This study aims to develop a reliable and relevant science literacy skills assessment instrument for 7th-grade junior high school students on the topic of global warming. The method used in this study is Research and Development (R&D) with the 4-D model, which consists of four steps: define, design, development, and disseminate. The subjects of the study consisted of 25 7th-grade junior high school students. The data collected included the validity, reliability, difficulty level, and discriminative power of the science literacy skills assessment instrument. The results of the study show that: (1) the instrument development steps include research and data collection, planning, draft product development, and design validation. However, the field trial, product refinement based on the field trial, and implementation were not conducted due to time constraints; (2) 14 items were declared valid; (3) the instrument’s reliability was obtained with a KR-20 value of 0.8046, which falls in the very high category; (4) the difficulty level of the questions is 53.3%, categorized as moderate (neither easy nor difficult); and (5) the discriminative power of the questions is categorized as sufficient. Thus, this instrument becomes an alternative that can be used by educators to assess students' science literacy skills.